Anatomy of the skull in the capybara (Hydrochoerus hydrochaeris) using radiography and 3D computed tomography - Pereira, Fernanda Mara Aragão Macedo [UNESP]; Bete, Stela Bonadia de Souza [UNESP]; Inamassu, Letícia Rocha [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Schimming, Bruno Cesar [UNESP] (Wiley, 2020)
The capybaras (Hydrochoerus hydrochaeris) are the largest rodent found throughout South America and are present in almost all the Brazilian territory, however, still lack basic descriptions about the species, such as about their cranial anatomy. This study was carried out to investigate the anatomical features in the capybara skull. Eight skulls and two heads, without sexual distinction, were used for the osteological, radiographic and tomographic identification of their structures. The skull of the capybara could be divided into a neurocranium and a viscerocranium. The capybara had a more robust and rectangular skull, elongated face caudally, thinned in the nasal region and slightly convex in the parietal region. The zygomatic arch was expanded and wide, the orbit had a circular shape, the infraorbital foramen was well developed, external acoustic meatus and tympanic bulla were relatively small, and the paracondylar process was large. These anatomical characteristics are compatible with the eating habit and semi-aquatic life of capybaras, which can be compared with characteristics reported for animals of similar habits. The radiographic image allowed to identify structures such as the frontal sinus, whereas 3D tomographic reconstruction was essential to have a spatial view of the skull of the capybara.
Keywords: caviomorph; osteology; radiology; rodent; tomography